Photosynthesis, Dry Matter Production and Partitioning in Cassava (Manihot esculenta Crantz) Under Partial Shade of a Coconut Plantation - Nedunchezhiyan, M.; Byju, G; Ravi, V (JOURNAL OF ROOT CROPS, 2013)
Photosynthetic rate of cassava (Manihot esculenta Crantz) varieties showed variation under partial shade of a coconut plantation at Coconut Research Station, Bhubaneswar, Odisha, India. The varieties, Sree Jaya, Sree Prakash, Sree Vijaya and H-165 had greater photosynthetic rate during the early crop growth period of 2 and 4 months after planting (MAP), which decreased later. Decrease in intercellular CO2 concentrations was observed during the later crop growth period in the above varieties. The intercellular CO2 concentrations had influenced the photosynthetic rate. Transpiration rate was observed to be maximum at 4 and 6 MAP when the crop was in the active growth period. Photosynthetic rate, intercellular CO2 concentrations and transpiration rate decreased with decrease in stomatal conductance. Among the varieties, Sree Jaya and H-165 showed higher dry matter production and partitioning to the tubers. Higher dry matter accumulation in shoot than in the tuber was observed in the varieties, Sree Prakash, M-4, Meg-36, H-226, H-97 and Sree Visakham. The photosynthetic rate exhibited strong and positive correlation with tuber bulking rate. Higher tuber yield was observed in Sree Jaya and H-165 due to more number of tubers per plant and tuber girth apart from greater biomass accumulation under partial shade.